Dexamethasone and Monophosphoryl Lipid A-Modulated Dendritic Cells Promote Antigen-Specific Tolerogenic Properties on Naive and Memory CD4+ T Cells - Maggi, Jaxaira; Schinnerling, Katina; Pesce, Bárbara; Hilkens, Catharien M.; Catalán, Diego; Aguillón, Juan C. (Frontiers in Immunology, 2016)
Tolerogenic dendritic cells (DCs) are a promising tool to control T cell-mediated autoimmunity. Here, we evaluate the ability of dexamethasone-modulated and monophosphoryl lipid A-activated DCs (MPLA-tDCs) to exert immunomodulatory effects on naïve and memory CD4+ T cells in an antigen-specific manner. For this purpose MPLA-tDCs were loaded with purified protein derivative (PPD) as antigen and co-cultured with autologous naïve or memory CD4+ T cells. Lymphocytes were re-challenged with autologous PPD-pulsed mature DCs (mDCs), evaluating proliferation and cytokine production by flow cytometry. On primed-naïve CD4+ T cells, the expression of regulatory T cell markers was evaluated and their suppressive ability was assessed in autologous co-cultures with CD4+ effector T cells and PPD-pulsed mDCs. We detected that memory CD4+ T cells primed by MPLA-tDCs presented reduced proliferation and pro-inflammatory cytokine expression in response to PPD and were refractory to subsequent stimulation. Naïve CD4+ T cells were instructed by MPLA-tDCs to be hyporesponsive to antigen-specific re-stimulation, and to suppress the induction of T helper cell type 1 and 17 responses. In conclusion MPLA-tDCs are able to modulate antigen-specific responses of both naïve and memory CD4+ T cells and might be a promising strategy to “turn off” self-reactive CD4+ effector T cells in autoimmunity.